2015
DOI: 10.7243/2055-091x-2-12
|View full text |Cite
|
Sign up to set email alerts
|

Perillyl alcohol inhalation concomitant with oral temozolomide halts progression of recurrent inoperable glioblastoma: a case report

Abstract: Aim: Glioblastoma multiforme (GBM), the most common and lethal primary brain tumor in adults, inevitably recurs despite standard of care, consisting of surgical resection, radiotherapy (RT), and alkylating temozolomide (TMZ). High content of the repair enzyme MGMT (O 6 -methylguanine-DNA methyltransferase) contributes to drug resistance and tumor recurrence. The monoterpene perillyl alcohol (POH) induces apoptosis and cytotoxicity of TMZ-resistant and TMZ-sensitive glioma cells independently of MGMT expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the meantime, other ongoing studies are building on the highly promising results obtained with intranasal POH by exploring respective combination approaches. For instance, a case study [111] reported a 51-year-old woman with inoperable GBM who had recurred after standard treatment with TMZ-based chemoradiotherapy and subsequently was enrolled in a clinical trial of intranasal POH concomitant with oral TMZ. After initiation of POH + TMZ, MRI scans revealed a marked reduction of the initially enhanced lesion, and no recurrences were noted over the following two years.…”
Section: Intranasal Poh As Monotherapymentioning
confidence: 99%
“…In the meantime, other ongoing studies are building on the highly promising results obtained with intranasal POH by exploring respective combination approaches. For instance, a case study [111] reported a 51-year-old woman with inoperable GBM who had recurred after standard treatment with TMZ-based chemoradiotherapy and subsequently was enrolled in a clinical trial of intranasal POH concomitant with oral TMZ. After initiation of POH + TMZ, MRI scans revealed a marked reduction of the initially enhanced lesion, and no recurrences were noted over the following two years.…”
Section: Intranasal Poh As Monotherapymentioning
confidence: 99%